Vahakn N. Dadrian. The Development of the Soviet Posture on Nationalities. (A Reappraisal of the Roles of Lenin and Stalin). A Paper Presented at the Section on Cultural and Racial Tensions and International Relations of the 6th World Congress of the International Sociological Association held in Evian, France - U. V, . (Revista Mexicana de Sociología, 1966)
reseña